2018
DOI: 10.1159/000491083
|View full text |Cite
|
Sign up to set email alerts
|

Multidose Methotrexate Treatment of Ectopic Pregnancies with High initial β-Human Chorionic Gonadotropin: Can Success Be Predicted?

Abstract: Objective: To investigate the clinical results and prognostic factors of multiple dose methotrexate (Mtx) treatment of ectopic pregnancy patients with high initial serum (human chorionic gonadotropin [hCG]). Design: Retrospective cohort study. Patients: Twenty-six ectopic pregnancy patients with serum (βhCG) > 5,000 mIU/mL who received multiple doses of Mtx (1 mg/kg) with folinic acid rescue on the alternating days. Results: Success rate was 88.5%. All failures were tubal ruptures in those who underwent surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Using a multidose MTX regimen, Tug et al observed that BMI, MTX dose, number of MTX injections and the decrement of β-HCG levels highly predictive for the success of the treatment. 22 An elevated initial β-HCG level is considered as the most important factor associated with treatment failure. The mean pretreatment β-HCG level for all patients in this study was 2016±2241IU/L, and the mean pretreatment level was 2.3 times higher in the failure group (4036±2940 vs 1734±1684 IU/L).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a multidose MTX regimen, Tug et al observed that BMI, MTX dose, number of MTX injections and the decrement of β-HCG levels highly predictive for the success of the treatment. 22 An elevated initial β-HCG level is considered as the most important factor associated with treatment failure. The mean pretreatment β-HCG level for all patients in this study was 2016±2241IU/L, and the mean pretreatment level was 2.3 times higher in the failure group (4036±2940 vs 1734±1684 IU/L).…”
Section: Discussionmentioning
confidence: 99%
“…Using a multidose MTX regimen, Tug et al observed that BMI, MTX dose, number of MTX injections and the decrement of β-HCG levels highly predictive for the success of the treatment. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate has been used in ectopic pregnancy [17] and to aid resorption of unresectable advanced extrauterine placentae. In advanced extra-uterine pregnancy, the variability of placental attachments calls for individualized decision-making and improvisation.…”
Section: Discussionmentioning
confidence: 99%
“…On day 3, blood results were as follows: WBC 4.150/μL, Hb 14.2 g/dL, β-hCG 4.165 IU/L. According to the hospital guidelines [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ], since β-hCG serum levels had not declined by more than 15%, the treatment continued in the same way. The patient received three more doses of MTX 100 mg on days 3, 5 and 7 and every dose was followed by administration of folinic acid 10 mg, on days 4, 6 and 8.…”
Section: Case Presentationmentioning
confidence: 99%
“…Methotrexate (MTX) can be administered via a single, double or multiple injections. Multiple-dose MTX treatment of cornual ectopic pregnancies appears to be a safe and effective method, but the success of the therapy depends strongly on body mass index, MTX dose, number of MTX injections and a decrease in β-hCG levels [ 14 ].…”
Section: Introductionmentioning
confidence: 99%